Cognitive distortions among Tishreen University employees (Journal of Hama University, 2024)
Introduction: Cognitive distortions refer to the obstacles that an individual may encounter in thinking and learning skills, among others. These lead to mood disorders that contribute to a decrease in his adaptation level, and affect the way he interprets events and how he deals with information. Aim: Determining the level of cognitive distortions and their relationship to some demographic data among Tishreen University employees. Methodology: A descriptive study was conducted on a random sample of 200 employees distributed equally among the faculties of nursing, human medicine, dentistry, and pharmacy. They were selected using the convenient sample method, and data was collected using two tools prepared by the researcher. Results: The results of the study showed that three-quarters of the sample had an average level of cognitive distortions. There are important differences in cognitive distortions due to the variables of college, age, marital status, educational level, and number of years of work, as Cognitive distortions were higher among employees in dentistry, younger employees, widows and divorced people, those with university education or above, and those with less than 5 years of work and 5-10 years. Recommendations: Developing training and awareness programs for employees aimed at improving awareness of cognitive distortions and promoting realistic and logical thinking, providing a work environment that encourages mental stimulation and innovation, providing counseling services and psychological support for them, and re-conducting this study on the employee population in all faculties of Tishreen University with a larger sample size.